Cell Cycle- and Vpr-Mediated Regulation of Human Immunodeficiency Virus Type 1 Expression in Primary and Transformed T-Cell Lines - Gummuluru, Suryaram (American Society for Microbiology, 1999)
Viral protein R (Vpr) of human immunodeficiency virus type 1 (HIV-1) transiently arrests cells in the G(2) phase of the cell cycle and is a weak transcriptional transactivator. We found that Vpr increased HIV-1 long terminal repeat (LTR) activity in all cells examined but, when expressed at high levels, decreased HIV-1 LTR expression due to cytotoxic effects. Moreover, Vpr-mediated enhancement of HIV-1 LTR-driven transcription was observed in cycling primary human CD4(+) T cells but not in terminally differentiated, noncycling primary human macrophages. In single-round infection experiments using primary human CD4(+) T cells, proviral clones expressing either wild-type Vpr or Vpr mutants that retained the ability to cause a G(2) arrest replicated to higher levels than proviruses lacking Vpr or expressing mutants of Vpr that did not cause an arrest. In support of the hypothesis that enhancement of HIV-1 LTR transcription by Vpr is an indirect effect of the ability of Vpr to delay cells in G(2), counterflow centrifugal elutriation of cells into different phases of the cell cycle demonstrated that HIV-1 LTR expression was highest in G(2). Finally, the ability of Vpr to upregulate viral transcription was dependent on a minimal promoter containing a functional TATA box and an enhancer.